Mass multiplication of Trichoderma harzianum on agricultural byproduets and their evaluation against seedling blight (Whizoctonia solano of mnngbean and collar rot (Sclerotiusn rokfsil) of groundnut - KATIUAR, K; DIXIT, G P; SINGH, B B (The Indian Journal of Agricultural Sciences, 2011)
Various low-cost agricultural waste products were screened for mass multiplication of T. harzianztm under normal storage condition and most effective formulated product of T. harzianum was evaluated in vivo and under field condition during 2005 and 2006 at West Bengal against seedling blight of mungbean (Rhizoctonia solani Kuhun) and collar rot of groundnut (Sclerotium rolfsi Sacc.) respectively. Wheat bran + mustard cake a20 % substrate was best in supporting growth and development as well as retention of appreciable population(x 1 08cfu/g) of antagonist under normal condition, followed by wheat bran + groundnut cake, rice bran + mustard cake and rice bran + groundnut cake. Highest percentage reduction in seedling blight of mungbean was recorded with wheat bran + mustard cake formulation of 2: hanianum(65.4%) and least with orange peel +mustard cake preparation. The lowest collar rot disease incidence in groundnut was observed with seed treatment followed by soil application of T. Aanianum @ 200 g along with farmyard manure @ 5.0 kg (T,) and yielded highest podslplant (21.9) and yield (3 080 kgha). The population of antagonist was also recorded highest in the rhizosphere soil of T, treatment.